THE ROLE OF PYROLYSIS TEMPERATURE FLUCTUATION ON LIQUID SMOKE FROM PALM SHELL - Neng Endah Jubaedah (Jurnal Scientia, 2023)
In this study, liquid smoke was pyrolyzed in a batch type pyrolysis reactor equipped with a stirrer to accelerate heat transfer during the process. In addition, cooling water that has been cooled by the refrigeration system is used during the smoke condensation process to produce liquid smoke. The research was conducted based on these supporting parameters to determine the effect of size, temperature, and pyrolysis time of palm shells on liquid smoke products. The method uses a pyrolysis process carried out in batches. Observations were made on the parameters of pyrolysis time, volume, pH, specific gravity (BJ), water content, acetic acid content, active compounds, and bacterial inhibition for each pyrolysis temperature interval, namely temperature 23 oC - 100 oC, 100 oC - 200 oC, 200 oC - 300 oC, and 300 oC - 400 oC. The test results stated that the amount and type of chemical produced causes the specific gravity of liquid smoke to increase with increasing pyrolysis temperature